PROMOSTION OF MOSQUITO REPELLENT PLANTS ON PKK RT 31 RW 07 DOLAHAN KELURAHAN PURBAYAN KOTAGEDE - Widia Rrahmatullah (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2018)
Mosquito repellents are a type of plant that can be used to dumb mosquitoes without first prosessing mosquito repellent can be used to repel mosquitoes because they contain highly unwanted compounds. The use of chemicals as a mosquito repellent in the long term can cause nause, shortness of breath and endanger cancer because chemicals accumulate. Some mosquito repellent plants that can be cultivated include lemongrass, lavender, zodia, geranium and rosemary. Growing mosquito repellent plants in addition to mosquitoes can also be used as ornamental plant. It is hiped that after ths counseling can increase the motivation of the cummunity to cultivate this mousquito repellent plant